Rice Os9BGlu31 Is a Transglucosidase with the Capacity to Equilibrate Phenylpropanoid, Flavonoid, and Phytohormone Glycoconjugates - Sukanya Luang; Jung‐Il Cho; Bancha Mahong; Rodjana Opassiri; Takashi Akiyama; Kannika Phasai; Juthamath Komvongsa; Nobuhiro Sasaki; Yanling Hua; Yuki Matsuba; Yoshihiro Ozeki; Jong‐Seong Jeon; et al. (2013)
Glycosylation is an important mechanism of controlling the reactivities and bioactivities of plant secondary metabolites and phytohormones. Rice (Oryza sativa) Os9BGlu31 is a glycoside hydrolase family GH1 transglycosidase that acts to transfer glucose between phenolic acids, phytohormones, and flavonoids. The highest activity was observed with the donors feruloyl-glucose, 4-coumaroyl-glucose, and sinapoyl-glucose, which are known to serve as donors in acyl and glucosyl transfer reactions in the vacuole, where Os9BGlu31 is localized. The free acids of these compounds also served as the best acceptors, suggesting that Os9BGlu31 may equilibrate the levels of phenolic acids and carboxylated phytohormones and their glucoconjugates. The Os9BGlu31 gene is most highly expressed in senescing flag leaf and developing seed and is induced in rice seedlings in response to drought stress and treatment with phytohormones, including abscisic acid, ethephon, methyljasmonate, 2,4-dichlorophenoxyacetic acid, and kinetin. Although site-directed mutagenesis of Os9BGlu31 indicated a function for the putative catalytic acid/base (Glu169), catalytic nucleophile residues (Glu387), and His386, the wild type enzyme displays an unusual lack of inhibition by mechanism-based inhibitors of GH1 β-glucosidases that utilize a double displacement retaining mechanism. Glycosylation is an important mechanism of controlling the reactivities and bioactivities of plant secondary metabolites and phytohormones. Rice (Oryza sativa) Os9BGlu31 is a glycoside hydrolase family GH1 transglycosidase that acts to transfer glucose between phenolic acids, phytohormones, and flavonoids. The highest activity was observed with the donors feruloyl-glucose, 4-coumaroyl-glucose, and sinapoyl-glucose, which are known to serve as donors in acyl and glucosyl transfer reactions in the vacuole, where Os9BGlu31 is localized. The free acids of these compounds also served as the best acceptors, suggesting that Os9BGlu31 may equilibrate the levels of phenolic acids and carboxylated phytohormones and their glucoconjugates. The Os9BGlu31 gene is most highly expressed in senescing flag leaf and developing seed and is induced in rice seedlings in response to drought stress and treatment with phytohormones, including abscisic acid, ethephon, methyljasmonate, 2,4-dichlorophenoxyacetic acid, and kinetin. Although site-directed mutagenesis of Os9BGlu31 indicated a function for the putative catalytic acid/base (Glu169), catalytic nucleophile residues (Glu387), and His386, the wild type enzyme displays an unusual lack of inhibition by mechanism-based inhibitors of GH1 β-glucosidases that utilize a double displacement retaining mechanism.